Anticipated nostalgia: Looking forward to looking back. Issue 3 (2nd April 2020) - Cheung, Wing-Yee; Hepper, Erica G.; Reid, Chelsea A.; Green, Jeffrey D.; Wildschut, Tim; Sedikides, Constantine
ABSTRACT: Anticipated nostalgia is a new construct that has received limited empirical attention. It concerns the anticipation of having nostalgic feelings for one's present and future experiences. In three studies, we assessed its prevalence, content, emotional profile, and implications for self-regulation and psychological functioning. Study 1 revealed that anticipated nostalgia most typically concerns interpersonal relationships, and also concerns goals, plans, current life, and culture. Further, it is affectively laden with happiness, sadness, bittersweetness, and sociality. Studies 2 and 3 assessed the implications of anticipated nostalgia for self-regulation and psychological functioning. In both studies, positive evaluation of a personal experience was linked to stronger anticipated nostalgia, and anticipated nostalgia was linked to savouring of the experience. In Study 3, anticipated nostalgia measured prior to an important life transition predicted nostalgia a few months after the transition, and post-transition nostalgia predicted heightened self-esteem, social connectedness, and meaning in life.